Molecular Phylogeny and Biogeographic History of the Armored Neotropical Catfish Subfamilies Hypoptopomatinae, Neoplecostominae and Otothyrinae (Siluriformes: Loricariidae) - Roxo, Fabio F. [UNESP]; Albert, James S.; Silva, Gabriel S. C. [UNESP]; Zawadzki, Claudio H.; Foresti, Fausto [UNESP]; Oliveira, Claudio [UNESP] (Public Library Science, 2014)
The main objectives of this study are estimate a species-dense, time-calibrated molecular phylogeny of Hypoptopomatinae, Neoplecostominae, and Otothyrinae, which together comprise a group of armoured catfishes that is widely distributed across South America, to place the origin of major clades in time and space, and to demonstrate the role of river capture on patterns of diversification in these taxa. We used maximum likelihood and Bayesian methods to estimate a time-calibrated phylogeny of 115 loricariid species, using three mitochondrial and one nuclear genes to generate a matrix of 4,500 base pairs, and used parametric biogeographic analyses to estimate ancestral geographic ranges and to infer the effects of river capture events on the geographic distributions of these taxa. Our analysis recovered Hypoptopomatinae, Neoplecostominae, and Otothyrinae as monophyletic with strong statistical support, and Neoplecostominae as more closely related to Otothyrinae than to Hypoptopomatinae. Our time-calibrated phylogeny and ancestral-area estimations indicate an origin of Hypoptopomatinae, Neoplecostominae, and Otothyrinae during the Lower Eocene in the Atlantic Coastal Drainages, from which it is possible to infer several dispersal events to adjacent river basins during the Neogene. In conclusion we infer a strong influence of river capture in: (1) the accumulation of modern clade species-richness values; (2) the formation of the modern basin-wide species assemblages, and (3) the presence of many low-diversity, early-branching lineages restricted to the Atlantic Coastal Drainages. We further infer the importance of headwater stream capture and marine transgressions in shaping patterns in the distributions of Hypoptopomatinae, Neoplecostominae and Otothyrinae throughout South America.